Монголчуудын эртний түүх бичлэгийн зарим онцлогоос (Археологийн судалгаан дээр) - Өлзийбаяр, С. (Historia Mongolarum, 2008)
Судар бичгийн хүрээлэнгээс түүх соёлын дурсгалыг олж илрүүлэх, бүртгэн тэмдэглэхээс эхэлсэн монголчуудын хийж ирсэн археологийн судалгаа нь өнөө үеийг хүрэхдээ хөгжлийн тодорхой үеүүдийг туулсаар иржээ. The archaeology of Mongolia has four periods in its history which differs from each other by research intensiveness of methods and theories of Marxist Leninist paradigm. 1.1921-1940. The foundation period. Arhaeological and ancient monuments were searched and redeem from defects with some interruptions. 2.1949-1969. The beginning period. The Mongolia's archaeology had been developed and several great works were published on Mongolian archaeology prime surveys. The our first archaeologists were born from the joint expedition of People's Republic of Mongolia and Soviet Union led by S.V.Kiselev and started surveys on paleolithic sites. The foundation year of Mongolia's archaeology is 1949 as the author's opinion. 3.1969-1989. The next period. The joint expedition of PR Mongolia and Soviet union had reached new level of archaeological survey. The basic theory books were published and ancient history problems were solved by the theory books diliberately. 4.Since 1990. Unknown Eastern archaeological theories and methods were introduced and were used by Mongolian archaeologists. The main centres and institutes of archaeological expeditions and surveys have been developed.